Coumarinolignans from the Seeds of Annona squamosa Linn. Issue 2 (2009) - Ranjan, Rakesh; Sahai, Mahendra
Abstract : Phytochemical investigations of Annona squamosa seeds have led to the isolation of three lignans consisting of coumarin moiety, cleomiscosin A (1), cleomiscosin B (2) and cleomiscosin C (3). Their structures were arrived at by detailed spectroscopic analysis. Cleomiscosin A and cleomiscosin B are position isomer.